Evaluating strategic periodisation in team sport - Robertson, S.; Joyce, D. (Journal of Sports Sciences, 2018)
The planned peaking for matches or events of perceived greatest priority or difficulty throughout a competitive season is commonplace in high-level team sports. Despite this prevalence in the field, little research exists on the practice. This study aimed to provide a framework for strategic periodisation which team sport organisations can use to evaluate the efficacy of such plans. Data relating to factors potentially influencing the difficulty of matches were obtained for games played in the 2014 Australian Football League season. These included the match location, opposition rank, between-match break and team "form". Binary logistic regression models were developed to determine the level of association between these factors and match outcome (win/loss). Models were constructed using "fixed" factors available to clubs prior to commencement of the season, and then also "dynamic" factors obtained at monthly intervals throughout the in-season period. The influence of playing away from home on match difficulty became stronger as the season progressed, whilst the opposition rank from the preceding season was the strongest indicator of difficulty across all models. The approaches demonstrated in this paper can be used practically to evaluate both the long- and short-term efficacy of strategic periodisation plans in team sports as well as inform and influence coach programming.